2022
DOI: 10.7150/jca.72973
|View full text |Cite
|
Sign up to set email alerts
|

The most effective but largely ignored target for prostate cancer early detection and intervention

Abstract: Over the past two decades, the global efforts for the early detection and intervention of prostate cancer seem to have made significant progresses in the basic researches, but the clinic outcomes have been disappointing: (1) prostate cancer is still the most common non-cutaneous cancer in Europe in men, (2) the age-standardized prostate cancer rate has increased in nearly all Asian and African countries, (3) the proportion of advanced cancers at the diagnosis has increased to 8.2% from 3.9% in the USA, (4) the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 128 publications
0
2
0
Order By: Relevance
“…Tenascin C is an extracellular matrix glycoprotein, which paves the paths and facilitates the migration and metastasis of breast cancer cells 117 - 119 . Our previous studies have shown that Tenascin C is also highly expressed at distinct degenerating prostate basal cells, and EP cells in the vicinity of areas with elevated Tenascin C often lose the cohesion 120 - 125 (Figure 13 ).…”
Section: B the Mecl Also Suffers From A Wide Variety Of Pathologic Al...mentioning
confidence: 91%
See 1 more Smart Citation
“…Tenascin C is an extracellular matrix glycoprotein, which paves the paths and facilitates the migration and metastasis of breast cancer cells 117 - 119 . Our previous studies have shown that Tenascin C is also highly expressed at distinct degenerating prostate basal cells, and EP cells in the vicinity of areas with elevated Tenascin C often lose the cohesion 120 - 125 (Figure 13 ).…”
Section: B the Mecl Also Suffers From A Wide Variety Of Pathologic Al...mentioning
confidence: 91%
“…Our hypothesis is very likely to be applicable to the invasion cascade observed in all EP-derived malignancies. Our previous studies of human prostate, lung, gastric, colorectal, skin, salivary gland, and cervical tumor tissues have consistently seen that the capsules of these tissues (especially the prostate tumor) harbor morphologically and immunohistochemically similar focal disruptions, which are associated with EP cell alterations that are essentially identical as those seen in the breast [109,110,[120][121][122][123][124][125].…”
Section: Amentioning
confidence: 99%
“…Positioned beneath the basal layer and separated by a basement membrane [51], the non-epithelial prostate microenvironment, collectively termed 'stroma', is composed of various cell types. The stroma is a complex cellular network that plays a vital role for normal prostate development and related diseases [52][53][54][55].…”
Section: Gene Expression According To Cell Typesmentioning
confidence: 99%
“…Autophagy is associated with multiple biological processes in PCa, and studies have shown that autophagy can promote the invasion and progression of PCa and simultaneously resist radiation-induced damage [6,8,9]. The cooperative effects of multiple cancer suppressor genes and oncogenes are involved in the development and metastasis of PCa [10,11].…”
Section: Introductionmentioning
confidence: 99%